A Harmful Care: The Association of Informal Caregiver Burnout With Depression, Subjective Health, and Violence. Issue 11 (June 2022) - Gérain, Pierre; Zech, Emmanuelle
Providing informal care to a relative can lead to informal caregiver burnout, which is expected to lead to deleterious consequences. Among these consequences lie the risk of perpetrating violent behaviors against the care-recipient, the caregivers' risk of depression, and their low subjective health. To investigate these associations, a sample of 499 informal caregivers completed a questionnaire addressing informal caregiver burnout, depression, subjective health, and violence. Hierarchical regression models were used to investigate the potential association of burnout with these potential consequences, while controlling for sociodemographic variables and received violence. The results show that burnout, and especially emotional exhaustion, is significantly associated with depression, low subjective health, and perpetrated physical violence, but not with perpetrated psychological violence. For both psychological and physical violence, it appears that receiving violence is one of the best predictors of perpetrating violence. With these results, this cross-sectional study confirms the association of informal caregiver burnout with deleterious consequences—even if this observation must be pondered—and the central role of received violence in predicting perpetrated violence, suggesting the risk of violence escalation. The implications of these results suggest that the emotional state of informal caregivers is one of the indicators of potential deleterious consequences and should, as such, be considered as a warning signal by field workers.